Diversity and Potential Active Compound of the Sponge-Associated Bacteria from Lemukutan Island, West Kalimantan Indonesia as New Type of Antibiotics - Baihaqi, M. Fikri; Nabila, Faika; Triwahyuni, Adelia; Fahira, Annisa Nasywa; Khairillah, Yuyun Nisaul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the diversity of sponge symbiont bacteria and the effectiveness of active compounds of bacteria that are symbiotic with marine sponges from Lemukutan Island waters. The methods in this study are isolation of sponge symbiont bacteria, characterization of sponge symbiont bacteria, antagonistic tests, activity tests of the best sponge symbiont bacterial isolate extract culture filtrate, and GCMS/MS tests. The results showed that nineteen isolates of sponge symbiont bacteria were successfully isolated from sponge types from Theonella cylindrica and Hyattella intestinalis sponges in Lemukutan waters. Seven isolates of sponge symbiont bacteria are included in the Gram-positive bacteria genre. While the other twelve are included in Gram-negative bacteria. Ten of the nineteen isolates of sponge symbiont bacteria have antibacterial activity for S. aureus. Isolate Sp4 10-6 B, based on the results of antagonistic tests, has an inhibition diameter of 10.28 mm, which is categorized as solid inhibition. Ethyl acetate extract of Sp4 10-6 culture filtrate has a minimum inhibitory concentration value of 0.5% against pathogenic bacteria S.aureus. The active compound with the potential for antibiotic development is the Tetradecane compound, which has the highest peak area of the eight other types of compounds. This shows that the concentration of the compound contained is higher than the other compounds. This compound is included in the aliphatic hydrocarbon and alkane groups.